The Shop in Dickens’s Fiction - Maria Teresa CHIALANT (E-REA)
All Dickens readers can easily agree that the presence of shops in his work is very striking, ranging from four “Scenes” in Sketches by Boz to better known examples like the eponymous place in The Old Curiosity Shop, Sol Gills’s store of nautical instruments in Dombey and Son, Krook’s warehouse in Bleak House and Mr. Venus’s laboratory in Our Mutual Friend to Household Words. Considering that shops are either buildings and rooms where goods and services are sold, or spaces stocked with merchandise for sale, the present article looks at the latter of these functions in Dickens’s fiction; its aim is twofold: to draw attention to their recurrence as containers of objects—which gives him the opportunity to satisfy his obsession with the naming of things and to adopt the stylistic device of the list—and to explore the homology between the shop and the page as an example of Dickens’s rhetoric of “excess.”